The field of the category of voice (Eurasian Journal of Philology Science and Education, 2016)
The article is devoted to determining the preconditions of studying the field of the category of voice. Voice is a functional-semantic category, it includes interacting language means (morphological, syntactic, lexical and grammatical and others), united by common semantic functions, belonging to the aspectual relations, the content of which is in transfer, character of performance and distribution of actions in time. In the area of general linguistics there are different views on the category of voice. Consideration of this category causes difficulties, which are due to the complexity of the functional-semantic field of the Turkic verb voice. There are also different approaches in Kazakhstani linguistics to the interpretation of this category. Due to the development of functional grammar of the Kazakh language the recent years have been marked by a profound interest in the functional-semantic research. Much effort has been done in this field. However, functional-semantic characterization of voice category has not been highlighted adequately yet. The author in the article provides the analysis of the central field and the micro field of the category of voice.
Keywords: voice; object; subject; verb; type; functional-semantic field.